Dynamic recrystallization kinetic of fine grained Mg-Zn-Y-Zr alloy solidified under high pressure - 樊志斌 林小娉 董允 李婵 王林 付守军 (Journal of rare earths, 2017)
Fine grained Mg_（96.17）Zn_（3.15）Y_（0.79）Zr_（0.18） alloy with an average grain size of 20 μm was prepared by high pressure solidification. The dynamic recrystallization（DRX） behavior of the fine grained Mg alloy solidified under the pressure of 4 GPa was studied via isothermal compression experiments. The tests were performed under the strain rate of 0.001–1.0 s~（–1） and at a deformation temperature of 523–623 K on a Gleeble-3500 D thermal-mechanical simulation machine. The DRX kinetic of the fine grained Mg alloy solidified under high pressure was established, and the microstructures of the alloy under different hot compression conditions were analyzed by electron back-scattering diffraction（EBSD）. According to the experimental results, the DRX kinetic model of the fine grain Mg alloy solidified under high pressure was X_（DRX）=1-exp[-0.75445（（ε-ε_c）/ε~＊）~（1.066208）.The Avrami exponents of n and k were 1.066208 and 0.75445 respectively, higher than those in the conventional casting alloy. The DRX volume fraction of the fine grain Mg alloy solidified under the pressure had a tendency to increase obviously with the strain rate decreasing and the deformation temperature increasing, which is different from the one in the conventional casting alloy. When compressed at 523 K, the DRX volume fraction of the fine grained Mg alloy solidified under high pressure was 85% under the strain rate of 1.0 s~（–1） and could be up to 95% under the strain rate of 0.001 s~（–1）. The DRX volume fraction of the conventional casting alloy was only 67% although under the condition of 623–0.001 s~（–1）. It was shown that the fine grained Mg alloy solidified under high pressure had a strong DRX capacity.